BIM contribution to labor safety in the construction industry: a systematic review of review - Taype, Lisseth Espinoza (Universidade Estadual de Campinas, 2020)
Between the years of 2012 and 2017, there were almost 97,000 accidents in Brazil in the construction industry. This is a significant quantity compared to other industries. These data reveal that the safety of the construction employees requires a change of approach, from the design phase through to the execution phase, including the use of new technologies, processes, and methodologies. In this sense, the adoption of Building Information Modeling (BIM) shows itself as a possible and effective response to such circumstances. This paper aims to present the results of a Systematic Literature Review (RSL) about the understanding of BIM regarding labor safety in the construction industry, as well as its application. To this end, the state of the art about the approaches and technologies employed in the area of occupational safety were raised, as well as gaps that open space for future research in this area. The paper considered the period from 2007 to 2019 and was conducted using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyzes). The data was systematized by StArt software. We reached the number of 97 studies that met the selection criteria. The results were categorized in order to identify the use of technologies and processes associated with BIM. Finally, 28 of the 97 articles confirmed a current tendency to identify risks early, especially in the collaborative project process. Therefore, the relevance of this work is to present a global panorama, showing alternatives to develop future research.